2017
DOI: 10.1177/1359104517730116
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic non-epileptic seizures in children and adolescents: Part II – explanations to families, treatment, and group outcomes

Abstract: Psychogenic non-epileptic seizures (PNES) – time-limited disturbances of consciousness and motor-sensory control, not accompanied by ictal activity on electroencephalogram (EEG) – are best conceptualized as atypical neurophysiological responses to emotional distress, physiological stressors and danger. Patients and families find the diagnosis of PNES difficult to understand; the transition from neurology (where the diagnosis is made) to mental health services (to which patients are referred for treatment) can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 21 publications
2
49
0
3
Order By: Relevance
“…The strongest and most important finding in this study is the raised prevalence of comorbidities involving psychiatric diseases (depression, anxiety) and in dissociative and somatoform conditions. Case-based observations have highlighted the high frequency of specific psychological profiles [5,[18][19][20][21], and the high rates of depression, anxiety, and somatoform conditions [18,22,23]. Somatoform patterns are also evident in this study as more patients showed a greater number of contacts with the healthcare system due to lipothymias, abnormal nonepileptic movements, symptoms of multiple organ system and minor traumas.…”
Section: Discussionmentioning
confidence: 57%
“…The strongest and most important finding in this study is the raised prevalence of comorbidities involving psychiatric diseases (depression, anxiety) and in dissociative and somatoform conditions. Case-based observations have highlighted the high frequency of specific psychological profiles [5,[18][19][20][21], and the high rates of depression, anxiety, and somatoform conditions [18,22,23]. Somatoform patterns are also evident in this study as more patients showed a greater number of contacts with the healthcare system due to lipothymias, abnormal nonepileptic movements, symptoms of multiple organ system and minor traumas.…”
Section: Discussionmentioning
confidence: 57%
“…Both adolescents showed symptoms associated with the respiratory system, e.g., difficult breathing and gasping. A recent study of children and adolescents with PNES showed that a significant percentage triggered their PNES via hyperventilation and showed abnormal regulation of PCO 2 [ 28 ]. In neither of the cases in this study was a blood CO 2 reading taken to assess for hypocapnia that could have been contributing to the dystonic symptom patterns and changes in level of consciousness [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there seems to be significant overlap between panic attacks, which involve abnormal breathing patterns, and psychogenic seizures [ 30 ]. It is possible that breathing interventions that targeted arousal, a decrease in respiratory rate, and normalization of ventilation and arterial CO 2 could have been helpful preventing or managing the PNES in the two adolescents described in this report [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study, Part I of a two-part article, presents the diagnostic formulations – the clinical formulations about the probable neurophysiological mechanisms, known or hypothesized – that were constructed for 60 consecutive children and adolescents with PNES who were referred to our Mind-Body Rehabilitation Programme for treatment. In Part II, we use the formulations presented here to frame discussions with patients and families, and to identify what treatments are most likely to help patients diagnosed with particular subtypes of PNES ( Kozlowska, Chudleigh, et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%